Activity of omadacycline in vitro against Clostridioides difficile and preliminary efficacy assessment in a hamster model of C. difficile-associated diarrhoea. (September 2022) - Leahy, Raina Gay; Serio, Alisa W.; Wright, Kelly; Traczewski, Maria M.; Tanaka, S. Ken
ABSTRACT: Objectives: Antibiotics are associated with increased risk of Clostridioides difficile infection, which has limited treatment options. We assessed in vitro activity of omadacycline (an aminomethylcycline antibiotic) against the C. difficile infection strain and efficacy in a hamster model of C. difficile -associated diarrhoea. Methods: Omadacycline, clindamycin, tigecycline, vancomycin, and metronidazole minimum inhibitory concentrations (MICs) for the infection-model strain ( C. difficile ATCC 43596) were determined. Hamsters were pretreated with subcutaneous clindamycin (10 mg/kg) and infected 24 h later with C. difficile ATCC 43596; 24 h post infection, they received oral omadacycline (50 mg/kg/day), vancomycin (50 mg/kg/day), or vehicle for 5 days. Efficacy was reported as survival. Results: Omadacycline was as active as tigecycline, vancomycin, and metronidazole (MIC 0.06 mg/L); clindamycin showed no activity. Median survival in hamsters was: 12 days, omadacycline; 2 days, vancomycin; 4 days, clindamycin pretreatment only. Conclusion: Omadacycline exhibited potent in vitro activity against C. difficile and showed efficacy in a model of C. difficile -associated diarrhoea.